A new species of Eukoenenia (Palpigradi: Eukoeneniidae) from Brazilian iron caves - Souza, Maysa F. V. R.; Ferreira, Rodrigo L. (Zootaxa, 2011)
Eukoenenia ferratilis sp. n. is described from 7 adults (6 females and 1 male) and 1 immature (stage A) collected in iron caves in the municipalities of Moeda and Brumadinho, Minas Gerais, Brazil. The new species shares characteristics with several species of the genus Eukoenenia Börner, 1901 being related to the species Eukoenenia mirabilis (Grassi & Calandruccio, 1885) and Eukoenenia berlesei (Silvestri, 1903), but the shape and chaetotaxy of the male and female genitalia are distinctive